Etiologies of fever of unknown origin in HIV/AIDS patients, Hanoi, Vietnam - Thu Kim Nguyen; Yen Hai Nguyen; Hao Thi Nguyen; Quang Minh Khong; Ngoc Kim Tran (BMC Infectious Diseases, 2022)
Abstract Background Fever of unknown origin (FUO) is a challenge for clinicians treating patients with HIV/AIDS. CD4 counts can be helpful in the diagnosis and treatment. This study aimed to determine several common etiologies of FUO stratified by CD4 count levels in HIV/AIDS patients. Methods A cross-sectional retrospective and prospective study was conducted in 195 HIV/AIDS patients with FUO admitted to the National Hospital for Tropical Diseases from January 2016 to June 2019. Clinical parameters, immune status, and etiologies for each patient were recorded. Odds ratios were calculated to compare the distributions of common etiologies in groups with two different CD4 count levels: < 50 cells/mm3 and ≥ 50 cells/mm3. Results The proportions of opportunistic infections and noninfectious etiologies were 93.3% and 3.6%, respectively. Tuberculosis was the most common opportunistic infection (46.7%), followed by talaromycosis (29.2%) and Pneumocystis jiroveci (PCP) infection (20.5%). Tuberculosis was predominant in all CD4 level groups. Most patients with talaromycosis had CD4 counts below 50 cells/mm3. In total, 53.8% of the patients were infected by one pathogen. The risks of tuberculosis and talaromycosis in FUO-HIV patients were high when their CD4 counts were below 50 cells/mm3. Conclusions Opportunistic infections, especially tuberculosis, are still the leading cause of FUO in HIV/AIDS patients. Tuberculosis and Talaromyces marneffei (TM) infection should be considered in patients with CD4 cell counts < 50 cells/mm3. This study implies that guidelines for appropriate testing to identify the etiology of FUO in HIV/AIDS patient based on the CD4 cell count should be developed, thereby reducing resource waste.